1985
DOI: 10.1002/1097-0142(19850301)55:5<1060::aid-cncr2820550523>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastrointestinal non-Hodgkin's lymphomas. A retrospective clinicopathologic study of 150 cases

Abstract: The records of 150 primary gastrointestinal (GI) lymphomas in adults collected from 1974 to 1982 at the Department of Pathology, University of Vienna, were reviewed. One hundred thirty‐three cases of malignant lymphomas (ML) were analyzed with respect to histologic type, presenting tumor stage, and clinical course, as well as for factors influencing prognosis. The histologic type of ML as assessed by the Working Formulation and the Kiel, the Lukes and Collins, and the Rappaport classifications showed only a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
58
1
6

Year Published

1987
1987
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(76 citation statements)
references
References 50 publications
11
58
1
6
Order By: Relevance
“…A second malignancy occurred in one case. (Gospodarowicz et al, 1983;Fleming et al, 1982;Paulson et al, 1983;Herrera et al, 1985;Dragosics et al, 1985;Ampil, 1987;Rosenfelt & Rosemberg, 1980;Economopoulos et al, 1985;Sheridan et al, 1985;Liang et al, 1987;Steward et al, 1985;Janus et al, 1984;List et al, 1988;Shepherd et al, 1988). Our study indicates that chemotherapy following surgical resection of gastrointestinal lymphomas is highly effective: we obtained 81% CRs in patients treated with partial or palliative resection, and an overall 76% 10-year causespecific survival, which are results comparable with those of other recently published reports (Paulson et al, 1983;Sheridan et al, 1985;Liang et al, 1987;Janus et al, 1984;List et al, 1988;Shepherd et al, 1988).…”
Section: Complicationscontrasting
confidence: 58%
See 1 more Smart Citation
“…A second malignancy occurred in one case. (Gospodarowicz et al, 1983;Fleming et al, 1982;Paulson et al, 1983;Herrera et al, 1985;Dragosics et al, 1985;Ampil, 1987;Rosenfelt & Rosemberg, 1980;Economopoulos et al, 1985;Sheridan et al, 1985;Liang et al, 1987;Steward et al, 1985;Janus et al, 1984;List et al, 1988;Shepherd et al, 1988). Our study indicates that chemotherapy following surgical resection of gastrointestinal lymphomas is highly effective: we obtained 81% CRs in patients treated with partial or palliative resection, and an overall 76% 10-year causespecific survival, which are results comparable with those of other recently published reports (Paulson et al, 1983;Sheridan et al, 1985;Liang et al, 1987;Janus et al, 1984;List et al, 1988;Shepherd et al, 1988).…”
Section: Complicationscontrasting
confidence: 58%
“…While several studies have emphasised the effectiveness of the complete surgical resection of localised lesions (Siegert et al, 1985;Fleming et al, 1982;Maor et al, 1984;Paulson et al, 1983), the majority of authors consider this therapeutic approach as non-curative. The clinical efficacy of adjuvant postoperative radiotherapy remains controversial (Herrmann et al, 1980;Hande et al, 1978;Gospodarowicz et al, 1983;Siegert et al, 1985;Paulson et al, 1983;Weingrad et al, 1982;Lim et al, 1977;Shimm et al, 1983;Herrera et al, 1985;Dragosics et al, 1985;Rao et al, 1984;Mittal et al, 1983;Ampil, 1987).…”
mentioning
confidence: 99%
“…Although the actual frequency of chemotherapy-related bleeding or perforation is not clear, the frequency of these complications in unresected patients with gastrointestinal lymphoma reported previously varies from 0% to 20% (Brooks et al, 1983;Gobbi et al, 1984;Rosenfelt et al, 1980). Another important aspect of surgery is tumour staging, and many authors have reported that this is the most important prognostic factor affecting survival (Lim et al, 1977;Shiu et al, 1982;Brooks et al, 1983;Dragosics et al, 1985;Hockey et al, 1987) Any additional treatment is based on the pathological stage, and surgical exploration with gastrectomy is the only means of achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…Although localized (stage I and II) primary gastric lymphoma (PGL) has been treated by various modalities, including surgery (Shiu et al, 1982), chemotherapy (Maor et al, 1984: Salles et al, 1991, surgery plus radiotherapy (Shiu et al, 1982;Gospodarowicz et al, 1983;Taal et al, 1993), surgery plus chemotherapy (Paulson et al, 1983;Sheridan et il, 1985;Shepherd et al, 1988;Bellesi et al, 1989;Pasini et al, 1994) and radiotherapy plus chemotherapy (Burgers et al, 1988;Dragosics et al, 1985, Maor et al, 1990Tondini et al, 1993), the best management for this disease is still unclear.…”
mentioning
confidence: 99%
“…In the Western countries gastrointestinal lymphomas comprise less than 20% of all non-Hodgkin's lymphomas ( I ) and less than 5% of all primary gastrointestinal malignancies (2,3), though there are regional and racial variations. Even in cases of uncommon malignancies the distinction of gastrointestinal lymphomas has become more important due to better awareness and increasing frequency of predisposing conditions (4).…”
mentioning
confidence: 99%